Midőn a vér… - Kőszegi, Edit; Simó, Sándor; Surányi, András (Hungary, 1994)
A film looks back at the notorious 1882 "blood libel" trials at Tiszaeszlar, Hungary, and examines the blood libel accusations after the Holocaust.
Duration: 01:18:00
Keywords: Documentary films